Human Rights, Violence Against Women, and Economic Development (The People’s Republic of China Experience) - Jordan, Ann D. (Columbia Journal of Gender and Law, 2019)
Human rights instruments and scholarship addressing the issues of violence against women and economic development fail to recognize that mainstream development projects directly impact upon the increasing levels of violence against women in the developing world. An unstated assumption in these instruments, and in most scholarship, is that economic development is a neutral, even a positive, force for change. Development adherents argue that the Western model of economic development is an a- historical, universal, neutral, and efficacious natural force for improving peoples’ well being and raising standards of living. This view has not gone unchallenged. Tinker, for one, has noted that “‘[p]olicymakers typically define the developmental process in terms of Western rationality and scientific knowledge,’ which are culturally limited and yet have been presented as universally valid.'” Nonetheless, until recently, women and men of almost every political and religious affiliation and every social, ethnic, and national/regional group around the world have touted economic development as a panacea for problems confronted by peoples in the developing world. Its proponents in the developed and developing world (mainly the elites) have forcefully promoted development as a means to pull ‘those backward peoples’ and countries out of their collective and individual misery and into the twentieth century. They cite economic reform as a precondition to the realization of the rewards of Western-style modernization, and democracy. In this way, economic development, modernization, and democracy emerge as an atheistic trinity. According to the trinity theory adherents, economic reform is the key to transforming authoritarian governments in developing countries into free-market, rights-based democracies. Mainstream development models, trinity adherents assure us, inevitably lead to (Western) modernity, which consists of an educated population with a civic consciousness that demands democratic political reforms. The assumptions underlying the theory have yet to be proven. This Article focuses on the economic prong of the trinity and attempts to link economic development to the increasing level of violence against women in the developing world. It also recommends changes to international human rights instruments and international lending practices. Additionally, it calls for research specifically targeted to uncover the process by which international development practices lead to acts of violence against women.